A sequencia didática como recurso metodológico no ensino de língua materna a partir das proposições da Olimpíada de Língua Portuguesa - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
This work is linked to the Research Group and Intervention in Reading, Writing and Literature at the school - LELIT and the Professional Master Program in Literature - PROFLE-TRAS. It aims to analyze, from the Didactic Sequences produced by Portuguese Language teachers within the scope of the PLO, that conceptions of language teaching have served as the basis for teaching Portuguese in school; what is meant by didactic sequence and what are the implications for their teaching / learning. To that end, we created a corpus of 12 didactic sequence proposals produced by teachers of basic education, made available on the web in external environments and internal to the Writing the Future Portal, proposals that aim at the teaching of genres circumscribed to the PLO, considering that it has served as significant reference for Portuguese language classes in Brazilian public schools. We see in these proposals, the intention of discussing a new vision for the teaching practices of LP, with this, we bring to make up this scenario of new possibilities, the proposals of teaching from the text and those that have the gender as object of teaching. We also study the concepts defended by the Language Teaching team of the Geneva School in the proposition of the Didactic Sequences, which has in Joaquim Dolz and Bernard Schneuwly their main representatives, as well as works that result from the adaptation of the SD model in the Brazilian educational reality. The results reveal divergences between the original SD model and the proposals produced by many teachers.
Keywords: Sequência Didática; Gênero textual; Ensino-aprendizagem; Olimpíada de Língua Portuguesa; CNPQ::CIÊNCIAS HUMANAS; LEITURA E PRODUÇÃO DE TEXTO; LINGUAGEM E LETRAMENTO